Johan Galtung Pioneer of Peace Research - Galtung, Johan; Fischer, Dietrich; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This is the first ever anthology of key articles by Johan Galtung, widely regarded as the founder of the academic discipline of peace studies. It covers such concepts as direct, structural and cultural violence; theories of conflict, development, civilization and peace; peaceful conflict transformation; peace education; mediation; reconciliation; a life-sustaining economy; macro-history; deep culture and deep structure; and social science methodology. Galtung has contributed original research, concepts and theories to more than 20 social science disciplines, including sociology, international relations and future studies, and has also applied his new insights in practice. The book is a valuable resource for researchers and practitioners, and can serve as a supplemental textbook for graduate and upper undergraduate courses in peace studies and related fields.
Keywords: Environmental sciences; Science -- History; Environmental law; Environment; Environmental Law/Policy/Ecojustice.; History of Science